2018
DOI: 10.21873/anticanres.12187
|View full text |Cite
|
Sign up to set email alerts
|

Should Adjuvant Radiation Therapy Be Systematically Proposed for Male Breast Cancer? A Systematic Review

Abstract: Breast cancer in males is infrequent, representing 1% of all breast carcinomas, and less than 1% of all male cancers (1, 2), even if its incidence seems to be increasing (3-7). All studies regarding male breast cancer (MBC) are retrospective and specific recommendations are sparse. The general management of non-metastatic MBC is usually based on guidelines for female breast cancer (FBC). Surgery, chemotherapy and hormonal therapy are based on classical prognostic factors. After mastectomy, which represents the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Because there is lack of prospective data on radiotherapy in MaBC, the recommendations for FeBC also apply to MaBC, to reduce locoregional failure, disease recurrence, and breast cancer mortality. In a recent study analyzing SEER data between 1998 and 2003, there was improved OS for case-matched patients who underwent postmastectomy radiotherapy (PMRT) (83% vs 54%, p < 0.001) [ 85 ]. Subgroup analysis in the same study also demonstrated improved OS in those with 1–3 lymph nodes (79% vs 72%, p < 0.05) as well as 4+ lymph nodes involved (73% vs 53%, p < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Because there is lack of prospective data on radiotherapy in MaBC, the recommendations for FeBC also apply to MaBC, to reduce locoregional failure, disease recurrence, and breast cancer mortality. In a recent study analyzing SEER data between 1998 and 2003, there was improved OS for case-matched patients who underwent postmastectomy radiotherapy (PMRT) (83% vs 54%, p < 0.001) [ 85 ]. Subgroup analysis in the same study also demonstrated improved OS in those with 1–3 lymph nodes (79% vs 72%, p < 0.05) as well as 4+ lymph nodes involved (73% vs 53%, p < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Adjuvant radiotherapy has been proven to increase local control in MBC patients following mastectomy. 26 It also improves OS, especially in men with positive lymph nodes. 26 In spite of these advantages, adjuvant radiotherapy remains underutilized.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the indications for post-surgical radiotherapy in MBC are the same as for female breast cancer [ 15 ]. Adjuvant radiation therapy is associated with improved survival, particularly in patients with positive lymph nodes [ 16 ]. In terms of systemic therapy, men with advanced breast cancer should be managed similarly to women.…”
Section: Discussionmentioning
confidence: 99%